PENGARUH STRUKTUR PENGENDALIAN INTERNAL TERHADAP KREDIT BERMASALAH PADA BANK BRI DI DENPASAR - Rista, Ni Putu Via; Widhiyani, Ni Luh Sari (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.09.TAHUN.2021DO - 10.24843/EEB.2021.v10.i09.p07, 2021)
This study aims to obtain empirical evidence of the effect of internal control on non-performing loans at Bank BRI in Denpasar. The population in this study were all employees of the Denpasar branch of BRI bank. The number of BRI banks in Denpasar is 18 banks. The sample in this study were several employees at each BRI bank in Denpasar Branch. The number of samples obtained consists of 64 respondents using a non-probability sampling method, namely purposive sampling technique. Data was collected by using the questionnaire method. The data analysis technique used is multiple linear regression analysis. Based on the results of this study, it shows that the internal control structure has a significant negative effect on non-performing loans at Bank BRI in Denpasar. The implication of this research is that it can contribute to the application of agency theory and behavioral theory and can provide input to banks to carry out better internal control to minimize non-performing loans.